CCK‐1 and CCK‐2 receptor agonism do not stimulate GLP‐1 and neurotensin secretion in the isolated perfused rat small intestine or GLP‐1 and PYY secretion in the rat colon. Issue 2 (26th January 2020) - Modvig, Ida M.; Christiansen, Charlotte B.; Rehfeld, Jens F.; Holst, Jens J.; Veedfald, Simon
Abstract: Gastrin and cholecystokinin (CCK) are hormones released from endocrine cells in the antral stomach (gastrin), the duodenum, and the jejunum (CCK). Recent reports, based on secretion experiments in an enteroendocrine cell line (NCI‐H716) and gastrin receptor expression in proglucagon‐expressing cells from the rat colon, suggested that gastrin could be a regulator of glucagon‐like peptide‐1 (GLP‐1) secretion. To investigate these findings, we studied the acute effects of CCK‐8 (a CCK1/CCK2 (gastrin) receptor agonist) and gastrin‐17 (a CCK2(gastrin) receptor agonist) in robust ex vivo models: the isolated perfused rat small intestine and the isolated perfused rat colon. Small intestines from Wistar rats ( n  = 6), were perfused intraarterially over 80 min. During the perfusion, CCK (1 nmol/L) and gastrin (1 nmol/L) were infused over 10‐min periods separated by washout/baseline periods. Colons from Wistar rats ( n  = 6) were perfused intraarterially over 100 min. During the perfusion, CCK (1 nmol/L), vasoactive intestinal peptide (VIP) (10 nmol/L), and glucose‐dependent insulinotropic polypeptide (GIP) (1 nmol/L) were infused over 10‐min periods separated by washout/baseline periods. In the perfused rat small intestines neither CCK nor gastrin stimulated the release of GLP‐1 or neurotensin. In the perfused rat colon, neither CCK or VIP stimulated GLP‐1 or peptide YY (PYY) release, but GIP stimulated both GLP‐1 and PYY release. In both sets of experiments, bombesin, a gastrin‐releasing peptide analog, served as a positive control. Our findings do not support the suggestion that gastrin or CCK participate in the acute regulation of intestinal GLP‐1 secretion, but that GIP may play a role in the regulation of hormone secretion from the colon. Abstract : Recent reports, based on secretion experiments in an enteroendocrine cell line (NCI‐H716) and gastrin receptor expression in proglucagon‐expressing cells from the rat colon, suggested that gastrin could be a regulator of glucagon‐like peptide‐1 (GLP‐1) secretion. To investigate these findings, we studied the acute effects of CCK‐8 (a CCK1/CCK2 (gastrin) receptor agonist) and gastrin‐17 (a CCK2(gastrin) receptor agonist) in the isolated perfused rat small intestine and the isolated perfused rat colon. Our findings do not support the suggestion that gastrin or CCK participate in the acute regulation of intestinal GLP‐1 secretion, but that GIP, unexpectedly, may play a role in the regulation of hormone secretion from the colon.